A C-terminal cationic fragment derived from an arginine-rich peptide exhibits in vitro antibacterial and anti-plasmodial activities governed by its secondary structure properties (2009)
The differential in vitro antimicrobial activity of a 12-residue-long arginine-rich peptide derived from protamine was examined against bacterial and parasite microbes. A design of discrete peptide fragments based on the thermolysin-digestion map allowed us to propose three peptide fragments to be further assessed regarding their biological and secondary structural properties. Peptide structure allowed designing three arginine-rich fragments. All peptide fragments were assessed regarding their antimicrobial activity against Gram-positive and Gram-negative bacteria and a human malaria strain. Qualitative and quantitative assays carried out for determining all peptides' antibacterial activity at different concentration levels included radial diffusion and a time-controlled technique. Tests demonstrated that all assessed molecules inhibited invasion of Plasmodium falciparum parasites to human red blood cells. Cytolytic activity of the parent protamine peptide was completely abolished by strategically fragmenting its aminoacid sequence. Remarkably, the cationic C-fragment exhibited stronger biological activity than its parent peptide. Interestingly, the peptide fragment denoted as 2077 displays a typical ?-helix profile according to its CD spectrum. The results support proposing the protamine C-terminal fragment as a potential new antimicrobial peptide. © 2009 Elsevier Inc. All rights reserved.